The The Impact of Earnings Management as for The Nigerian Listed Firms Financial Reporting Quality on Information Asymmetry: THE IMPACT OF EARNINGS MANAGEMENT AS FOR THE NIGERIAN LISTED FIRMS FINANCIAL REPORTING QUALITY ON INFORMATION ASYMMETRY - Saheed Ademola Lateef; Norfadzilah Nik Mohd Rashid; Umar Aliyu Mustapha; Abdallah Bala Ado (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2019)
Earnings management is one of the critical issues related to financial reporting quality, particularly after the Enron and WorldCom scandals. Earnings management behaviors are related to the low level of corporate social responsibilities (CSR) and improvement in both areas would be expected to result to Improvements in the quality of financial reporting (FR). Hence, the aims and objective of this study is to examine the impact of earnings management as financial reporting quality on information asymmetry for the listed firms, Nigeria. The study is a conceptual paper on the relationship between earnings management of financial report and information asymmetry of Nigerian listed firms. Based on constructing the underlying theoretical framework of earnings management, the relationship between earnings management and information asymmetry is studied. The study revealed that both real earnings quality and accruals earning quality models are relevant to understanding the financial reports, that is, lower information asymmetry challenge. Therefore, uninformed users of financial reports are encouraged to rely on financial analysts in order to make efficient portfolio decisions. Also, if there is any need for the management of listed companies to use earnings manipulation, real earnings manipulation is recommended for them rather than the accrual-based approach. Finally, the study suggests that other researcher(s) can go beyond this to put retail and institutional on one side, and foreign investors on the other side, then focus on each group in separate studies.